Concurrent enhancement in fire retardancy and mechanical properties of flax/vinyl ester bio-composites via magnesium hydroxide incorporation - Rizwan Ahmed Malik (PLoS ONE, 2025)
The fire-retardant properties of bio-composites are generally enhanced through nano fillers incorporation at the cost of their mechanical properties. In this study, magnesium hydroxide (MH) nano filler was incorporated into flax/vinyl ester (VE) bio-composite to enhance its fire-retardancy and thermal stability simultaneously with mechanical properties. MH is chemically compatible with cellulosic fibers which played a role in improving the interfacial bonding and hence the mechanical properties in this study. The composites fabrication process parameters including curing temperature and vacuum pressure were also optimized in this study. The concentration of MH was varied as 0, 5, and 10% in the flax/VE composite. The tensile and flexural strengths of the 5% MH filled flax/VE composites were observed to increase by 10% and 48% respectively. This enhancement in strength was attributed to the improved interfacial bonding and compatibility of MH with flax fiber, verified through Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transformed Infrared Spectroscopy (FTIR), respectively. The horizontal burning rate of the composites was decreased by 25% after MH incorporation, which was validated through a limiting oxygen index (LOI) test. The results of cone calorimetry highlighted a decrease of 11.73% in the peak values of heat release rate (HRR) which is a sign of enhancement in fire retardancy. The thermogravimetric analysis also discovered an improvement in the thermal stability of the composites. These bio-composites with improved mechanical, thermal and fire-retardant properties may find their applications in automobiles, marine and aerospace industries.